Exploring the Structure of Job Satisfaction and Its Impact on the Satisfaction-Performance Relationship - Wagner, Stephen H. (Journal of Organizational Psychology, 2017)
This research assessed the structure of job satisfaction and examined its impact on the satisfactionperformance relationship. Seventy-five employees of a midwestern university completed a survey assessing global job satisfaction, job cognitions, negative job affect, and positive job affect. Supervisors of these employees rated their job performance, organizational citizenship behaviors focused on the organization (OCB-O), and organizational citizenship behaviors focused on individuals (OCB-I). Positive job affect was positively related to both in-role performance and OCB-Os. Job cognitions and positive job affect had positive relations with OCB-Is. A three-way interaction between global job satisfaction, job cognitions, and negative job affect predicted OCB-Is.